Reducing microglial lipid load enhances β amyloid phagocytosis in an Alzheimer's disease mouse model - Wu, Xiaoting (2025)
Macrophages accumulate lipid droplets (LDs) under stress and inflammatory conditions. Despite the presence of LD-loaded macrophages in many tissues, including the brain, their contribution to neurodegenerative disorders remains elusive. This study investigated the role of lipid metabolism in Alzheimer's disease (AD) by assessing the contribution of LD-loaded brain macrophages, including microglia and border-associated macrophages (BAMs), in an AD mouse model. Particularly, BAMs and activated CD11c+ microglia localized near β amyloid (Aβ) plaques exhibited a pronounced lipid-associated gene signature and a high LD load. Having observed that elevated intracellular LD content correlated inversely with microglial phagocytic activities, we subsequently inhibited LD formation specifically in CX3CR1+ brain macrophages using an inducible APP-KI/Fit2iΔMφ transgenic mouse model. We demonstrated that reducing LD content in microglia and CX3CR1+ BAMs remarkably improved their phagocytic ability. Furthermore, lowering microglial LDs consistently enhanced their efferocytosis capacities and notably reduced Aβ deposition in the brain parenchyma. Therefore, mitigating LD accumulation in brain macrophages provides perspectives for AD treatment.